Continuous Positive Airway Pressure Reduces Night-Time Blood Pressure and Heart Rate in Patients With Obstructive Sleep Apnea and Resistant Hypertension: The RHOOSAS Randomized Controlled Trial - Joyeux-Faure, Marie; Baguet, Jean-Philippe; Barone-Rochette, Gilles; Faure, Patrice; Sosner, Philippe; Mounier-Vehier, Claire; Lévy, Patrick; Tamisier, Renaud; Pépin, Jean-Louis (Frontiers in Neurology, 2018)
Objective. Most patients with resistant hypertension (RH) have obstructive sleep apnoea (OSA). We aimed to determine the impact of OSA and continuous positive airway pressure (CPAP) treatment on the leptin profile and blood pressure (BP) in patients with resistant hypertension (RH). Methods. After an initial case control study (RH with and without OSA), we performed a randomized, single blind study in OSA + RH patients receiving either sham CPAP (3-months) followed by active CPAP (6 months) or 6 months of active CPAP. The primary outcome was the comparison of leptin levels between groups of resistant hypertension patients with or without OSA. Secondary outcomes were the comparison of metabolic parameters, biomarkers of sympathetic activity and blood pressure indices between the two groups of resistant hypertension patients with or without OSA. The same outcomes were then evaluated and compared before and after sham and effective CPAP intervention. Results. Sixty-two patients (60 ± 10 years; 77% men) with RH (24-hour daytime SBP / DBP: 145 ± 13 / 85 ± 10 mmHg, 3.7 antihypertensive drugs) were included. The 37 RH patients exhibiting OSA (60%) were predominantly men (87 vs 64% for non-OSA patients), with a greater prevalence of metabolic syndrome and higher creatininemia. Their leptin concentrations were significantly lower than in non-OSA patients (9 [6 ; 15] vs 17 [6 ; 29] ng/mL) but increased after six months of CPAP. Three months of effective CPAP significantly decreased night-time SBP by 6.4 mmHg and heart rate by 6.0 bpm, compared to sham CPAP. Conclusions. The association between OSA and RH corresponds to a specific predominately male phenotype with a higher burden of metabolic syndrome and higher creatininemia but there was no significant difference between OSA and non-OSA patients regarding BP indices, and the number of anti-hypertensive drugs used. Active CPAP could be efficient at decreasing night-time BP and heart rate but there was no difference between CPAP and sham CPAP groups for all metabolic and SNS markers (NCT00746902 RHOOSAS).